PENGARUH JUS BUAH MANGGIS (Garcinia mangostana L.) TERHADAP PROFIL FARMAKOKINETIK PARASETAMOL PADA TIKUS PUTIH JANTAN (Rattus norvegicus) GALUR WISTAR - ., Emy Oktaviani (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2013)
Drug interaction happen when drugs is given together with foods. This researchwas aimed to observe the effect of mangosteen juice to the paracetamol pharmacokineticprofile in Wistar male white rats. The study was using male Wistar rats weight 200-350 g.The animals were divided into three groups with the total of the male rats are 15. Group I(paracetamol) was given a single oral paracetamol 9 mg/200gBW. Group II (treatment 1)was given a single oral paracetamol 9 mg/200gBW together with mangosteen juice 2,88g/200gBW. Group III (treatment 2) was given a single oral paracetamol 9 mg/200gBWtogether with mangosteen juice 0,66 g/200gBW. The serial blood was collected from tailvein for 9 hours and were analyzed using spectrophotometer UV for unchangedparacetamol. The pharmacokinetic parameters of paracetamol were calculated byrecidual method and were analyzed by One Way ANOVA using 95 % confidenceinterval. The difference between groups were analyzed using Post Hoc LSD-test. Theresults showed that the group II (paracetamol-mangosteen 1) and group III (paracetamolmangosteen2)increased of ka, Cpmaks, t, tab, ke, tel, CL, AUC and decreased ofka, ke, and CL. The research showed that mangosteen juice doses 2 give higher decreasedmetabolism and decreased elimination of paracetamol in rat.maksKey words : Mangosteen fruit, Pharmacokinetics, Paracetamol, Drug interaction